Broker-dealer risk appetite and commodity returns - Erkko Etula (Federal Reserve Bank of New York, 2010)
This paper shows that the risk-bearing capacity of U.S. securities brokers and dealers is a strong determinant of risk premia in commodity markets. Commodity derivatives are the principal instrument used by producers and consumers of commodities to hedge against commodity price risk. Broker-dealers play an important role in this hedging process because commodity derivatives are traded primarily over the counter. I capture the limits of arbitrage in this market in a simple asset-pricing model where producers and consumers of commodities share risk with broker-dealers who are subject to funding constraints. In equilibrium, the price of aggregate commodity risk decreases in the relative leverage of the broker-dealer sector. I estimate the model in the cross-section of commodities and find strong empirical support for its predictions. Fluctuations in risk-bearing capacity have particularly strong forecasting power for energy returns, both in sample and out of sample.
Keywords: G10; G12; G13; G24; 330; Asset pricing; financial intermediaries; commodity prices; futures markets; risk appetite